2014
DOI: 10.1130/g35940.1
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for degassing during the lava dome eruption of Mount St. Helens 2004–2008

Abstract: The ability of volatiles to escape rising magma regulates the explosivity of a volcanic system. During silicic lava dome eruptions, strain localization at the conduit margin occurs during magma ascent, creating a damage halo with implications for gas escape. Here we report the first systematic study of permeability network anisotropy across the marginal shear zone of the A.D. 2004-2008 lava dome at Mount St. Helens (Washington State, USA). The results show increasingly large permeability anisotropy of as much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…We showed that in highly crystalline magmas, fracture networks control not only the magnitude but also the location and direction of fluid movement (Gaunt et al 2014). We found that permeability was highly anisotropic in the shear fractured rocks at conduit margins, but broadly isotropic in the column interior.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…We showed that in highly crystalline magmas, fracture networks control not only the magnitude but also the location and direction of fluid movement (Gaunt et al 2014). We found that permeability was highly anisotropic in the shear fractured rocks at conduit margins, but broadly isotropic in the column interior.…”
Section: Introductionmentioning
confidence: 79%
“…1). Water permeability measurements made at room temperature and an effective pressure of 10 MPa also show that permeability is independent of sample orientation (Gaunt et al 2014), indicating that the fluid transport properties of this lava dome block are also broadly isotropic.…”
Section: Acoustic Wave Velocitiesmentioning
confidence: 84%
See 3 more Smart Citations